Unveiling Clutch Investment Strategies in Birds: A Case Study on Great Tits Using Generalized Additive Models - Lluís Socias‐Martínez; Elena Álvarez; Louise R. Peckre; Emilio Barba (Ecology and Evolution, 2025)
ABSTRACT Reproductive effort involves trade‐offs among offspring and with homeostasis. In birds, a crucial parental investment concerns the allocation of resources to each egg. Variation in egg investment has led to the development of hypotheses regarding whether females favor the eldest nestlings (“brood reduction”) or distribute resources more evenly (“brood survival”). Alternative explanations include the maturation of reproductive organs and trade‐offs with environmental constraints, such as thermoregulation. The earliest tests of these hypotheses relied on the deviation of the last egg's volume from the clutch mean (D). More recent studies have often overlooked non‐linearity and temporal autocorrelation in egg investments. Here, we analyze 145 broods comprising 1084 eggs from a great tit (Parus major) population in eastern Spain using generalized additive mixed‐effects models (GAMMs). Laying order influenced egg volume, with most variation occurring as an increase from the first to middle eggs in the clutch, followed by a slight decrease. We favor the interpretation that females adopt a brood survival strategy because (1) volume changes were of small magnitude (approx. 5%); (2) no significant negative effects of the number of eggs developing simultaneously in the ovary, total clutch size, or minimum temperatures were found; and (3) the laying order effect prevailed throughout the breeding season. However, within this brood survival strategy, females slightly favored middle eggs. In addition, negative correlations among deviations in volume from the main strategy suggest that energetic trade‐offs were present. Finally, most variation occurred between clutches, reinforcing previous findings of limited plasticity in egg volume in birds. Our results further caution against relying on mean egg volume (D) as a measure of investment strategies and highlight the importance of considering non‐linearity and temporal autocorrelation in analyses of reproductive investment. The use of GAMMs provides a robust approach to overcoming previous analytical limitations in the study of within‐clutch variation in egg investment.